ROLE ASSESSMENT OF INTEREST GROUP IN THE FORMULATION OF EDUCATION POLICY AND PRACTICE IN NIGERIA: The PTA and NUT Account towards Education Productivity and Quality Teaching - A. A., Isma’il Musa (Sokoto Educational Review, 2020)
This paper assesses the role of interest group in the formulation of education policy and practice in Nigeria. Having in mind that the government reserves the rights and privilege of making this decision to itself the influence and proposition of interest groups had been a force to be reckon with in the field of educational practice in Nigeria. In most cases, the activities of the group checks, moderates and a times nullified intentions and actions of the government. Particularly, with reference to the Nigeria Union of Teachers [NUT] and Parent- Teachers Association [PTA] activities who are prominent players in the first two levels of our education system. Attempt is made in this paper to review the activities of these groups and how they fa re respectively as moderators of policies in the sector. It is recommended that interest group should continue to keep up their inevitable roles and have their ears-on-ground so that they can immediately respond to any issue, policy and reform of government that may be detrimental or incongruent to the group interest and for the general purpose.